INVESTIGATING THE STUDENTS' VALUE ORIENTATIONS IN THE LEARNING ENVIRONMENT OF THE HIGHER SCHOOL - Natalya Ye. Zhdanova (Russian State Vocational Pedagogical University, 2015)
The research objective is investigation of value orientation system and its development in the context of social and professional personality growth in the higher school.Methods: For diagnosing the value sphere, the author applies the morphological life value tests of V.F. Sopov and L.V. Karpushina, and C.S. Bubnov's diagnostic method of the actual value orientation structure.Results: The research findings demonstrate a significant potential of vocational education environment for fostering the students' life values due to the organized and structured educational processes, and involved psychological and pedagogical teaching techniques. Additionally, the author emphasizes the interrelation between a student's capability of living in the present, flexible behavior, and self-awareness, - on the one hand, and such values as a family, financial position, achievements, social contacts and creativity.Scientific novelty: The research identifies the development dynamics of students' value orientation in the course of university studies with regard to the gender differences.Practical significance: The identified specificities of students' value orientation dynamics can be used for planning the content of training sessions and extracurricular activities.